Lack of Multidrug Resistance-associated Protein 4 Prolongs Partial Hepatectomy-induced Hepatic Steatosis. (24th April 2020) - Donepudi, Ajay C; Smith, Gregory J; Aladelokun, Oladimeji; Lee, Yoojin; Toro, Steven J; Pfohl, Marisa; Slitt, Angela L; Wang, Li; Lee, Ji-Young; Schuetz, John D; Manautou, José E
Abstract: Multidrug resistance-associated protein 4 (Mrp4) is an efflux transporter involved in the active transport of several endogenous and exogenous chemicals. Previously, we have shown that hepatic Mrp4 expression increases following acetaminophen overdose. In mice, these increases in Mrp4 expression are observed specifically in hepatocytes undergoing active proliferation. From this, we hypothesized that Mrp4 plays a key role in hepatocyte proliferation and that lack of Mrp4 impedes liver regeneration following liver injury and/or tissue loss. To evaluate the role of Mrp4 in these processes, we employed two-third partial hepatectomy (PH) as an experimental liver regeneration model. In this study, we performed PH-surgery on male wildtype (C57BL/6J) and Mrp4 knockout mice. Plasma and liver tissues were collected at 24, 48, and 72 h postsurgery and evaluated for liver injury and liver regeneration endpoints, and for PH-induced hepatic lipid accumulation. Our results show that lack of Mrp4 did not alter hepatocyte proliferation and liver injury following PH as evaluated by Ki-67 antigen staining and plasma alanine aminotransferase levels. To our surprise, Mrp4 knockout mice exhibited increased hepatic lipid content, in particular, di- and triglyceride levels. Gene expression analysis showed that lack of Mrp4 upregulated hepatic lipin1 and diacylglycerol O-acyltransferase 1 and 2 gene expression, which are involved in the synthesis of di- and triglycerides. Our observations indicate that lack of Mrp4 prolonged PH-induced hepatic steatosis in mice and suggest that Mrp4 may be a novel genetic factor in the development of hepatic steatosis.